TI_GERICHTE 15.2022.98 vom 7. September 2022 , Ricorso contro la graduatoria nel fallimento. Termine di ricorso - TI Tribunale d'appello (2022)
Ricorso contro la graduatoria nel fallimento. Termine di ricorso